Analysis of the Potential and Challenges of Nature-Based Sport Tourism in West Java - Gilang Pratama Putra; Enjang Yusup Ali; Dalia Susilawati (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
West Java is endowed with diverse natural landscapes—mountains, rivers, and forests—that offer strong potential for the development of sport tourism. As interest in nature-based and adventure tourism grows, especially among younger generations, the region has an opportunity to foster innovative and sustainable tourism models. This study adopts a descriptive qualitative approach to explore perceptions and challenges related to sport tourism in West Java. The research involved university students with a demonstrated interest in tourism and sports, selected for their responsiveness to emerging travel trends. Data were collected through questionnaires focusing on two key dimensions: natural potential and development challenges. Findings show that students generally view West Java as highly suitable for sport tourism, citing its natural richness and varied landscapes. However, several obstacles were identified, including inadequate infrastructure, limited safety regulations, and weak digital promotion. These challenges suggest the need for a more integrated strategy that aligns environmental potential with institutional and promotional support. Strengthening both ecological and managerial aspects will be essential in positioning sport tourism as a prominent driver of regional development and identity in West Java.